Occurrence of Influenza A (H1N1) in Alagoas (2016-2019)/ Ocorrência de Influenza A (H1N1) em Alagoas (2016-2019) - Ellen Karollyne Santos Lopes; Allana Caroline Bonfim Costa; Karoline Barbosa Gomes; Samara dos Santos Oliveira; Tariqat Sofia Machado Montiel; Claudimary Bispo dos Santos (Universidade Estadual de Alagoas, 2020)
: Influenza A is a viral respiratory tract disease, which is transmitted on a large scale by the Myxovirus influenzae virus, through person-to-person contact by dissemination of droplets containing viral particles. Among influenza A subtypes, the H1N1 and H3N2 subtypes are those that are in active circulation among humans. The main symptoms arising from the infection are high fever, muscle pain, headache, cough and tiredness. In this context, the present study aimed to quantify the cases of Influenza A of the subtype H1N1, in the State of Alagoas, during the period from 2016 to the first half of 2019. Data were collected through a search on the Ministry of Health website of SARS cases for influenza A of the H1N1 subtype registered in epidemiological reports. In Alagoas, 2016 presented the highest number of cases of H1N1, 52 cases and 12 deaths, while in 2017 there was the lowest expressiveness, with 06 positive cases and 03 deaths. In 2018, 32 cases of H1N1 and 03 deaths were reported. In the first half of 2019, 21 cases and 3 deaths were confirmed, but 37 cases and 05 deaths are still being investigated. According to the data obtained, it was concluded that, in 2016, the H1N1 viral disease in Alagoas was more expressive, whereas in 2017, there were few cases, as was also observed in the country in general.